Eco-friendly synthesis of lignin-based nanoparticles as antifungal agent - Marshallanore, Amat; Chin, Suk Fun; Mohd Effendi, Wasli; Ngieng, Ngui Sing; Awang Ahmad Sallehin, Awang Husaini (Elsevier B.V., 2023)
In this study, lignin (LNPs) and iodo-lignin nanoparticles (ILNPs) with mean particle sizes of 215 nm and 360 nm were synthesized by a nanoprecipitation method. Both LNPs and ILNPs exhibited excellent antifungal efficacy against various fungi such as Cunninghamella sp., Fusarium equiseti, Penicillium chermesinum, Aspergillus flavus, Aspergillus niger and Trichoderma piluliferum. LNPs demonstrated an inhibition effect ranging from 25.81% to 65.29% whereas ILNPs exhibited a superior inhibition effect ranging from 81.34% to 95.57%. This work has proven that both LNPs and ILNPs are promising eco-friendly nano-fungicides for plant pathogenic fungi.